SADC’S PURSUIT OF MARITIME SECURITY IN A REGION LACKING REGIONALISM - Walker, Timothy (Scientia Militaria - South African Journal of Military Studies, 2020)
Southern African Development Community (SADC) member states participate in many regional and multilateral initiatives that aim to enhance collective maritime security. How these initiatives affect state behaviour, and how African states’ interests and values, in turn, shape the functioning of these initiatives remain underexplored in maritime security studies. In addition, the study investigated the significance of SADC-focused regionalism as a force for its member states as they develop and implement foreign policies concerning maritime security in the region.